$zilch.00 [insurance policy] - Abalone Alliance::::::::: (1980)
Flier designed by the Abalone Alliance to parody an insurance policy premium issued by the Price-Anderson Nuclear Insurance Co., 'a subsidiary of holocaust, plunder and waste enterprises.' Other text that appears on the first page reads: 'if the shoe doesn't fit we'll chop your leg off'; 'after us the deluge'; 'there is nothing to fear, everything is under control'; 'let them eat plutonium'; 'in case of disaster place premium on top of your head so as to avoid fall out contamination'; 'we kill now you pay later'.